Perhtiungan, Pemungutan, dan Pelaporan Pajak PPh 21 Karyawan (Studi Kasus Pada PDAM Tirta Alam Tarakan - Nuh Khalif Kamil; Cornelius Rantelangi Rantelangi; Raden Priyo Utomo (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This study aims to determine the compliance of the calculation, collection, and reporting of Article 21 PPh employees in PDAM of Tarakan from June to September 2018. The type of research used in this study is quantitative, namely data in the form of numbers or data that can be calculated as well as can be analyzed systematically. The quantitative data in this study are the numbers contained in the Calculation of Income Tax Article 21 which is an overview and salary of company employees in 2018. These data are sourced through primary data, and the techniques used in data collection use the method of observation and library research. The results of this study are 1. The tax calculation carried out by PDAM Tirta Alam of Tarakan has not been in accordance with the Article 21 PPh calculation rules according to Law No. 36 of 2008. Because there are differences in the calculation of office fees, 2. Calculation of taxes carried out by PDAM Tirta Alam Kota Tarakan is not yet in accordance with the Article 21 PPh calculation rules according to Law No. 36 of 2008. Because there are differences in the calculation of PPh 21 on Holiday Allowances (THR), 3. Reporting and depositing taxes carried out by PDAM Tirta Alam Tarakan City is in accordance with regulations according to Law No. 36 of 2008.